THE KEEPING QUALITY OF THE PASTEURIZED MILK PRODUCED IN THESSALONIKI - GREECE - ΠΑΝΕΤΣΟΣ Α.; ΚΑΡΑΙΩΑΝΝΟΓΛΟΥ Π.; ΜΑΝΤΗΣ Α. (Journal of the Hellenic Veterinary Medical Society, 1973)
The keeping quality of the pasteurized milk produced in the district of Thessaloniki was examined. It was found that pasteurized milk which was stored at 4° C, continued to have the same bacterial counts, low acidity, and no off flavours after 48 hours. The results were compared with those obtained from samples of milk collected from different stores.